2021
DOI: 10.1101/2021.11.30.21267063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Role of Financial Support Programs in Mitigating the Sars-CoV-2 Spread in Brazil

Abstract: We calculate the impact of a socioeconomic program during 2020 as a measure to mitigate the Coronavirus Disease 2019 (COVID-19) outbreak in Brazil. For each Brazilian State, we estimate the time-dependent reproduction number from daily reports of COVID-19 infections and deaths using a Susceptible-Exposed-Infected-Recovered-like (SEIR-like) model. Then, we analyse the correlations between the reproduction number, the amount of individuals receiving governmental aid, and the index of social isolation based on mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…We identified a further four studies published after the review searches were undertaken (Albani et al 2021, Bourdeaux et al 2021, Homaie Rad et al 2021, Johnson et al 2022). Alongside the five studies identified from reviews, a total of nine primary studies are included in this report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a further four studies published after the review searches were undertaken (Albani et al 2021, Bourdeaux et al 2021, Homaie Rad et al 2021, Johnson et al 2022). Alongside the five studies identified from reviews, a total of nine primary studies are included in this report.…”
Section: Resultsmentioning
confidence: 99%
“…Two epidemiological modelling studies evaluated whether there was a reduction in COVID-19 transmission due to an increase in social isolation (Albani et al 2021, Pichler et al 2020). Pichler et al (2020) estimated the impact of unconditional sick leave to support individuals who may need to self-isolate in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…The model accounts for the following five compartments, susceptible (S), exposed (E), infected (I), recovered (R) and deceased (D). The progress between the compartments is defined by the dynamical system of ordinary differential equations below [26]: normaldSnormaldt=βfalse(tfalse)SI, normaldEnormaldt=βfalse(tfalse)SIσE, normaldInormaldt=σEfalse(γfalse(tfalse)+δfalse(tfalse)false)I, normaldRnormaldt=γfalse(tfalse)I 2emand2emnormaldDnormaldt=δfalse(tfalse)I.The time-dependent transmission parameter is denoted by β ( t ) and the infection to onset mean time is represented by 1/ σ , which is set to 5.1 days [27]. The quantity γ denotes the recovery rate and δ ( t ) is the death rate.…”
Section: Methodsmentioning
confidence: 99%
“…The model accounts for the following five compartments, susceptible (S), exposed (E), infected (I), recovered (R), and deceased (D). The progress between the compartments is defined by the dynamical system of ordinary differential equations below [26]: The time-dependent transmission parameter is denoted by β ( t ) and the infection to onset mean time is represented by 1 /σ , which is set to 5.1 days [27]. The quantity γ denotes the recovery rate and δ ( t ) is the death rate.…”
Section: Methodsmentioning
confidence: 99%
“…The model accounts for the following five compartments, susceptible (S), exposed (E), infected (I), recovered (R), and deceased (D). The progress between the compartments is defined by the dynamical system of ordinary differential equations below [26]:…”
Section: Describing the Disease Spread Dynamicsmentioning
confidence: 99%